Design principles for result-based, collective and value chain-based environment and climate contract solutions in agriculture and forestry: Learning from 44 case studies across Europe - T. Eichhorn; T. Runge; D. Viaggi; J. Kantelhardt; F. Bartolini; T. Bradfield; P. Dupraz; K.S. Harmanny; A. Iglesias; F. Le Gloux; E. Majewski; A. Malak-Rawlikowska; et al. (Land Use Policy, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Reply to: A commentary on Holocene relative sea-level histories of far-field islands in the mid-Pacific - Fangyi Tan; Aron J. Meltzner; Tanghua Li; Jędrzej M. Majewski; Nicole S. Khan; Peter M. Chutcharavan; Benjamin P. Horton (Quaternary Science Reviews, 2025)

Development of a harmonized and risk-based code system for post-mortem inspection of broilers - Michał Majewski; Lis Alban; Désirée S. Jansson; Thomai Lazou; Nina Langkabel; Dragan Antic; Eija Kaukonen; Helena Wall; Madalena Vieira Pinto; Laila Østergaard; Ole Gyvelgaard Nielsen; Sergio Ghidini; et al. (Food Control, 2024)

Decreased vascular contraction and changes in oxidative state in middle–aged Wistar rats after exposure to increased levels of dietary zinc - Małgorzata Borkowska-Sztachańska; Michael Thoene; Katarzyna Socha; Jerzy Juśkiewicz; Michał S. Majewski (Toxicology and Applied Pharmacology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sediment analysis and historical context of the 2018 Palu-Donggala tsunami deposit, Indonesia - Jędrzej M. Majewski; Adam D. Switzer; Rachel Y.S. Guan; Benazir Benazir; Ella Meilianda; Peter R. Parham; Robert Weiss; Stacey S. Martin; Lillian K. Pearson; Jessica E. Pilarczyk; Patrick Daly; Benjamin P. Horton (Marine Geology, 2023)

Glacial Isostatic Adjustment modelling of the mid-Holocene sea-level highstand of Singapore and Southeast Asia - Tanghua Li; Stephen Chua; Fangyi Tan; Nicole S. Khan; Timothy A. Shaw; Jedrzej Majewski; Aron J. Meltzner; Adam D. Switzer; Patrick Wu; Benjamin P. Horton (Quaternary Science Reviews, 2023)

Mapping ways of detecting and handling antimicrobial residues in pigs and pig meat in- and outside Europe - L. Alban; B. Antunović; M. Belous; S. Bonardi; R.M. García-Gimeno; I. Jenson; A.H. Kautto; M. Majewski; D. Oorburg; I. Sakaridis; A. Sirbu; M. Vieira-Pinto; et al. (Food Control, 2023)

Holocene relative sea-level histories of far-field islands in the mid-Pacific - Fangyi Tan; Nicole S. Khan; Tanghua Li; Aron J. Meltzner; Jędrzej Majewski; Nicholas Chan; Peter M. Chutcharavan; Niamh Cahill; Matteo Vacchi; Dongju Peng; Benjamin P. Horton (Quaternary Science Reviews, 2023)

Circumpolar genetic population structure of polar cod, Boreogadus saida - R. J. Nelson; C. Bouchard; L. Fortier; A. R. Majewski; J. D. Reist; K. Præbel; M. L. Madsen; G. A. Rose; S. T. Kessel; G. J. Divoky (Polar Biology, 2020)

A comparison of the trophic ecology of Beaufort Sea Gadidae using fatty acids and stable isotopes - J. D. Brewster; C. Giraldo; E. S. Choy; S. A. MacPhee; C. Hoover; B. Lynn; D. G. McNicholl; A. Majewski; B. Rosenberg; M. Power; J. D. Reist; L. L. Loseto (Polar Biology, 2018)

Trophic variability of Arctic fishes in the Canadian Beaufort Sea: a fatty acids and stable isotopes approach - Carolina Giraldo; Ashley Stasko; Emily S. Choy; Bruno Rosenberg; Andrew Majewski; Michael Power; Heidi Swanson; Lisa Loseto; James D. Reist (Polar Biology, 2016)

Widespread intra-specific genetic homogeneity of coastal Antarctic benthic foraminifera - Wojciech Majewski; Samuel S. Bowser; Jan Pawlowski (Polar Biology, 2015)
Benthic foraminifera are a major component of the Antarctic biota. Coastal foraminiferal morphospecies are widely distributed in Antarctic waters. The question is whether these morphotypes are genetically identical or, rather, they represent a cohort of cryptic species. Here, we compared genetically nine benthic foraminiferal morphospecies from Admiralty Bay (South Shetlands) and the western Ross Sea (McMurdo Sound, Terra Nova Bay), separated by a distance of ~4500 km. Additionally, for three of these morphospecies, we included specimens from Rothera (Marguerite Bay), which is located between the two main areas of interest. Our study, based on SSU and ITS rDNA sequence data, shows that all examined morphospecies share the same genotypes despite the presence of considerable intra-individual genetic variability.

A novel rearrangement of occludin causes brain calcification and renal dysfunction - Marissa A. LeBlanc; Lynette S. Penney; Daniel Gaston; Yuhao Shi; Erika Aberg; Mathew Nightingale; Haiyan Jiang; Roxanne M. Gillett; Somayyeh Fahiminiya; Christine Macgillivray; Ellen P. Wood; Philip D. Acott; et al. (Human Genetics, 2013)

Genetic differentiation between Arctic and Antarctic monothalamous foraminiferans - Jan Pawlowski; Wojciech Majewski; David Longet; Jackie Guiard; Tomas Cedhagen; Andrew J. Gooday; Sergey Korsun; Andrea A. Habura; Samuel S. Bowser (Polar Biology, 2008)

Micrometeorologic Methods for Measuring the Post-Application Volatilization of Pesticides - M. S. Majewski (Water, Air, & Soil Pollution, 1999)